Exploring the implementation of the merdeka curriculum in biology education: A qualitative study at an Indonesian upper secondary school - Tarigan, Mhd. Rafi'i Ma'arif; Azis, Suhartini; Lase, Natalia Kristiani; Tarwiyani, Tarwiyani (Universitas Islam Negeri Sumatera Utara, 2025)
This study aims to describe the implementation of the Merdeka Curriculum in Biology learning at SMA Negeri 1 Sibolga and to analyze its supporting and inhibiting factors. The study was conducted in the odd semester of the 2024-2025 academic year using a descriptive qualitative approach. Data collection techniques included observation, interviews, and documentation. The results show that the implementation of the Merdeka Curriculum in Biology was carried out gradually. Teachers showed strong enthusiasm and initiative in understanding and applying curriculum principles such as differentiated learning and project-based learning. The school supported this effort by providing a Biology laboratory, digital learning resources, and internal training. However, several challenges emerged, including unequal teacher understanding of the curriculum, difficulties in preparing teaching materials aligned with the learning outcome, and limited practical training. Learning evaluation was conducted regularly through formative assessments and classroom observations. Routine reflection served as a crucial means of improving instruction. The study concludes that the success of curriculum implementation is strongly influenced by teacher readiness, school support, and active student engagement. Strengthening teacher capacity and inter-teacher collaboration is recommended as a strategic step to optimize curriculum implementation.